Assessing the sustainability of government debt: On the different states of debt/GDP process - Anton Velinov (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper discusses the type of trajectory a country's public debt path follows. In particular, a Markov switching ADF model is used to assess the sustainability of public debt by testing whether a government's present value borrowing constraint holds. Building on the work of Raybaudi et al. (2004) and Chen (2011), the model in this paper generalizes their methodology. The number of lags and states are in principle unrestricted and all of the parameters can be switching. Debt trajectories of 16 countries are investigated using long time series on debt/GDP obtained from Reinhart and Rogoff (2011). Two different criteria are used to test the null hypothesis of a unit root in each state. The countries with a sustainable debt path are found to be Finland, Norway, Sweden, Switzerland and the UK, while Greece and Japan are found to have unsustainable debt trajectories. The debt paths of the remaining countries are mainly characterized as being in a unit root state and are therefore labeled as uncertain. Robustness tests indicate that the model is robust to the sample size and the number of states used. Further, it is shown that the models used in this paper offer an improvement to existing models investigating this subject.
Keywords: C22; C24; H60; 330; Markov switching; debt trajectory; debt sustainability; unit root